Perilaku Konsumen Terhadap Keputusan Pembelian Dengan Peran Citra Merek Sebagai Variabel Moderasi - Liantifa, Melifia (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT - SEKOLAH TINGGI ILMU EKONOMI SAKTI ALAM KERINCI, 2018)
This study aims to test: 1) How the influence of consumer behavior on purchasing decisions in CV. AMKA Kerinci Provinsi Jambi, 2) How is the influence of brand image to purchase decision in CV. AMKA Kerinci Provinsi Jambi, 3) What is brand image acts as a moderator between consumer behavior and purchasing decisions. Population in this research is all consumer of Urea Powder Pink Powder CV. AMKA Kerinci Provinsi Jambiwith a sample of 60 respondents with sampling technique incidental sampling. Data were collected through questionnaires with Likert Scale analyzed by qualitative descriptive method and quantitative descriptive. The data analysis tools used are Response Achievement Level (RAL), Moderated Regression Analysis (MRA), determination koefisien, t test and F test with SPSS for Windows software version 22.0. Based on the results of research and hypothesis test results show that: 1) Consumer behavior affect the purchase decision of pureed pink urea fertilizer CV. AMKA Kerinci Provinsi Jambiwith significant value 0,001 < 0,05.2) Brand image have an effect on purchasing decision of urea pink bag of pink CV. AMKA Kerinci Provinsi Jambi with significant value 0,000 < 0,05. 3) Brand image act as a moderating variable between consumer behavior toward purchasing decision of urea pink bag of pink. CV. AMKA Kerinci Provinsi Jambi with significant value 0,025 < 0,05.